The Position of Expert Witnesses in Medical Malpractice Cases in Indonesia - Hatta, Muhammad (Faculty of Shariah and Law, State Islamic University (UIN) Walisongo, 2018)
Medical malpractice is one of the most difficult professional errors to prove. In solving medical malpractice cases, law enforcement is always assisted by doctors by connecting experts to reveal the truth with their expertise. The position of doctors as experts is very important and strategic. However, it is not easy for a doctor who wants to become a expert witness because the relationship of the suspect is a colleague. If the doctor want to be an expert witness then his testimony in court is not objective or impressed protect his colleagues. This study suggests that in the completion of medical malpractice cases in court can apply the system of proof by changing the proof to the doctor. In addition, this study also suggests to resolve medical malpractice cases that can be solved through the way of mediation before pursuing litigation settlement. In the aspect of Islamic law, the position of expert witness (ra`yu al-khÄbir) is very important to explain or interpret a case that is vague and difficult to prove. However, an evidentiary system unable to prove the medical malpractice case then Islamic law can justify by using other methods that can bring benefit in general.[]Malpraktik medik adalah salah satu kesalahan professional yang sangat sulit dibuktikan. Dalam menyelesaikan kasus malpraktik medik, penegak hukum selalu dibantu oleh dokter sebagai saksi ahli untuk mengukapkan kebenaran sesuai dengan keahlian yang dimilikinya. Kedudukan dokter sebagai saksiahli sangat penting dan strategis. Namun, tidak mudah mendapatkan dokter yang mau menjadi saksi ahli terhadap tersangka karena saksi ahli dengan tersangka adalah teman sejawat. Apabila dokter mau menjadi saksi ahli maka kesaksiannya di pengadilan dinilai tidak objektif atau terkesan melindungi teman sejawatnya. Penelitian ini menyarankan supaya dalam penyelesaian kasus malpraktik medik di pengadilan dapat menerapkan sistem pembuktian terbalik dengan memindahkan beban pembuktian kepada dokter. Selain itu, penelitian ini juga meÂnyarankan supaya penyelesaian kasus malpraktik medik dapat diselesaikan melalui jalur mediasi sebelum menempuh penyelesaian secara litigasi. Dalam aspek hukum islam, kedudukan saksi ahli (ra`yu al-khÄbir) sangat penting untuk menerangkan atau menafsirkan suatu perkara yang kabur dan sulit dibuktikan. Namun, apabila sistem pembuktian dengan menggunakan saksi ahli tidak mampu membuktikan perkara malpraktik medik maka hukum islam dapat membenarkan menggunakan metode lain yang dinilai dapat mendatangkan maslahat secara umum.